IMPLEMENTASI PENGISIAN FORMULIR INFORMED CONSENT KASUS BEDAH UMUM SEBAGAI SALAH SATU BUKTI TRANSAKSI TERAPEUTIK DI RSUD DR. SOEKARDJO KOTA TASIKMALAYA TAHUN 2017 - Lina Khasanah Khasanah (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
According to the Ministry of Health Decree No. 129 of 2008 concerning Minimum Standards Services in Hospitals, filling Informed Consent (IC) forms must be 100%. Preliminary study addressing 15 IC form of general surgery case in January 2017 wasn’t filled complete. Purpose of the research is for knowing how the implementation filling of the IC form general surgery cases as evidence of therapeutic transactions in Dr. Soekardjo Tasikmalaya city hospital on 2017.The method of research is descriptive with mixed method approach, a total sample is 127 IC form, and the research participant is a general surgeon, chief medical record unit, nurse and patient.The result showed that the average percentage of completeness IC form of the general surgery cases in the first quarter of 2017 was 68.9%. Inhibitory factors are limited time, lack of human resources, priority on BPJS patient, lack of socialization, priority on high risk patients, no follow-up analysis, oral IC is considered easier, and delay in medical record control. The supporting factors are communication, application of accreditation, time lag of action. So average percentage of IC filling still below the SPM standard. Hospital should improve the causal factors that inhibit the incompleteness of IC and maintain the supporting factor, so IC can be filled completely